1073. Sulbactam-Durlobactam Has Potent Activity Against Multidrug-Resistant Acinetobacter baumannii Clinical Isolates From Thai Patients With Chronic Infections. (4th December 2021) - Wannigama, Dhammika Leshan; Higgins, Paul G; Hurst, Cameron; Abe, Shuichi; Hongsing, Parichart; Luk-In, Sirirat; Kueakulpattana, Naris; Laowansiri, Matchima; Tanasatitchai, Chanikan; Srisakul, Sukrit; Kicic, Anthony; Chatsuwan, Tanittha; et al.
Abstract: Background: Due to the increase in multi-drug resistance (MDR) of Acinetobacter baumannii chronic infections with accompanying considerable morbidity and mortality, it is imperative to find effective novel treatments. Durlobactam (DUR) is a potent broad-spectrum inhibitor of Ambler classes A, C and D serine β-lactamases that effectively restores sulbactam (SUL) activity against MDR A.baumannii isolates. SUL-DUR is currently in late-stage development for the treatment of infections caused by Acinetobacter spp., including drug resistant isolates. In this study, we sought to evaluate potency of SUL-DUR against MDR A. baumannii isolates collected from Thai patients with chronic infections. Methods: Non-duplicative clinical strains were isolated during 2016–2019 from 200 chronically infected patients in different medical wards with a variety of different infections at King Chulalongkorn Memorial Hospital, Bangkok, Thailand. Susceptibility testing of SUL-DUR and comparator agents was performed according to CLSI guidelines. SUL-DUR was also tested on a background of imipenem (IPM) therapy (SUL-IPM titrated at a 1:1 ratio plus DUR fixed at 4 mg/L). Data analysis was performed using CLSI and EUCAST breakpoint criteria where available. Results: This collection of isolates was 92% sulbactam-resistant (using a breakpoint of 4 mg/L), 91% carbapenem-resistant, 74% amikacin resistant and 8% colistin resistant. In contrast, the SUL-DUR MIC90 was 4 mg/L compared with 64 mg/L for sulbactam alone. SUL-DUR was equally potent across antibiotic-resistant subsets. Only 6 isolates (3%) had SUL-DUR MIC values >4 mg/L. Interestingly, addition of imipenem to SUL-DUR showed similar potency as SUL-DUR alone, with an MIC90 of 2 mg/L. Conclusion: SUL-DUR showed potent in vitro activity against contemporary clinical isolates from a hospital in Bangkok, Thailand. If successfully developed, SUL-DUR may be an important new therapeutic option for the treatment of MDR Acinetobacter infections. Disclosures: Alita Miller, PhD, Entasis Therapeutics (Employee)